Is the University Universal? Mobile (Re)Constitutions of American Academia in the Gulf Arab States. (March 2015) - Vora, Neha
<x xml:space="preserve">Abstract</x> Through ethnographic examples of students' engagement with American universities in the United Arab Emirates and Qatar, I argue that branch campuses have a particularly important relationship with emerging forms of racial consciousness, identity, and politicization among students, both citizen and foreign resident. This entry point is one that deliberately foregrounds the parochialism of an American perspective on the future of the academy as part of a broader project of postcolonial and transnational engagement with this new knowledge economy.